Out of sight - Leonard, Elmore, 1925-2013 (Delacorte Press, 1996)
A bank robber in Florida commandeers a car belonging to a woman U.S. marshall, climbs with her into the trunk, while an accomplice drives. So begins a novel about two people who really wish the ride had gone forever. As it is, she escapes to lead a manhunt for him.